PENGARUH PENGGUNAAN MEDIA POP UP BOOK TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI KERAGAMAN BUDAYA KELAS IV SEKOLAH DASAR SE-KELURAHAN BANYUANYAR - Tamarin Wahyu Retnaningtyas; Anggit Grahito Wicaksono; Mukhlis Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The backdground of the problem in this research is based on observations made by the researcher that during the learning process, the teacher has not used media, resulting in students lacking understanding of the material presented. The purpose of this research is to determine the impact of using pop up book media on students learning outcomes in the subject of cultural diversity in fourt grade elementary school. The research used a quantitative experimentak research method with a One Group Pretest Posttes Design. This study employed a data collection instrument consisting of 20 multiple-choice question, conducting normality tests, homogeneity tests, and hypothesis test, the result of the research on the effect of using pop up book media in elementary school obtained a pretest score of 50,9615 and a posttest score os 931731, indicating an increase in learning outcomes of 32,2116. The result of the Paired Sample T-Test hypothesis test obtained a t-value > v-table or 30,182 > 1,67528, this study states that Ha is accepted and Ho is rejected, and there is an effect of using pop up book media on the learning outcomes of students in the subject of cultural diversity in grade IV elementary school.